Hubungan Intensitas Penggunaan Gadget dengan Kualitas Tidur Anak Usia Sekolah di SD Negeri 5 Manistutu - Ni Ketut Ayu Puspayanti; I Gusti Ayu Putu Satya Laksmi; Putu Gede Subhaktiyasa (Jurnal Riset Kesehatan Nasional, 2026)
Introduction : Sleep quality is an important component in supporting the growth and development of school-age children, while increasing the intensity of gadget use in this age group has the potential to disrupt rest patterns and reduce sleep quality. This study aims to analyze the relationship between the intensity of gadget use and the sleep quality of school-age children in SD Negeri 5 Manistutu. Methods: This study used a correlational descriptive design with a cross-sectional approach and involved 69 respondents through a total sampling technique. The research instruments used were a questionnaire on the intensity of gadget use and the Pittsburgh Sleep Quality Index (PSQI). Relationship analysis was carried out using the Chi-Square test. Results: The results showed that most children had a high intensity of gadget use (69.6%) and poor sleep quality (94.2%). The Chi-Square test showed a significance value of p < 0.001 which indicates a meaningful relationship between the intensity of gadget use and the sleep quality of school-age children, with the distribution of data showing that children with medium and high gadget use were all in the category of poor sleep quality. Discussion : These results indicate that the higher the intensity of gadget use, the more likely the child is to experience poor sleep quality. These findings can be the basis for educational efforts and regulations on the use of healthier gadgets for school-age children. Keywords: School-age children, Intensity of gadget use, Sleep quality